Data Mining Untuk Menguji Relevansi Keberadaan Prasyarat Mata Kuliah - Yetli Oslan; Harianto Kristanto; Raden Gunawan Santosa (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
A good curriculum is an important part of an academic process. The curriculum in the Information Systems Department is grouped 5 (five) knowledge clusters, one of which is the Database cluster which will be used in this research. The Database cluster consists of 5 (five) courses, namely SI1433 [Information System Analysis and Design], SI1443 [Database Systems], SI2323 [Database Design], SI3433 [Data Warehousing], SE4323 [Data Mining]. The purpose of this research is to see the relevance of the existence of prerequisite courses in courses in the Database sciences group. Relevance was measured from the independence test of pairs of 2 (two) courses based on the chi-square distribution statistical test. If the course pair shows dependency, then the existence of prerequisites is considered appropriate, whereas if the results show independence, then the prerequisites are not needed. The final conclusion from this research is that the pairs of 5 subjects studied are all dependent except for courses SI1433 (Information System Analysis and Design) and SI3433 (Data Warehousing) with a significant probability value of 0.265. So implementing the prerequisite courses in the Database cluster in the UKDW Information Systems department is relevant.